Cancer-associated retinopathy preceding the diagnosis of a pulmonary carcinoid tumour. Issue 11 (2nd November 2020) - Merle, Geoffrey; Baglivo, Edoardo; Younossian, Alain B; Vijgen, Sandrine; Karenovics, Wolfram; Kherad, Omar
Abstract : Cancer-associated retinopathy (CAR) belongs to the paraneoplastic retinopathy syndromes and manifests itself by rapidly progressive vision loss, scotoma and photopsia. We herein reported the case of a 77-year-old woman without a cancer history who presents typical CAR symptoms. A complete workup followed by lung biopsy enabled the detection of a pulmonary carcinoid tumour. Treatment of oral cortisone was then initiated with dramatic improvements in the symptoms.